Peran “Voice of SWCU” dalam Brand Awareness dan Peningkatan Intake - Pujani, Chenanjah Refa; Wijaya, Lina Sinatra (Jurnal Pustaka Komunikasi, 2025)
Brand awareness is essential for higher education institutions to build a positive image and attract prospective students. This study aims to analyze the role of public relations through Voice of SWCU as an internal medium of Satya Wacana Christian University (UKSW) in developing brand awareness and its contribution to increasing student intake. This research employs a mixed-method approach with data collected through online questionnaires, observations, interviews, FGDs, and documentation. The findings reveal three primary roles of the Voice of SWCU. First, as a communication facilitator, the Voice Publication and Documentation Team and UKSW Promotion Division build interactive communication through social media. Second, as a problem solver, the management of Voice resolves internal issues that affect the external image. Third, as a communication technician, the Voice PDD Team and UKSW Promotion Division create creative content that enhances visibility. The levels of brand awareness show relatively balanced results with Top of Mind (37%), Brand Recall (35%), Brand Recognition (28%), and Unaware of Brand (0%). These findings emphasize that internal media, such as a high-achieving student activity unit, can be an effective public relations strategy to build brand awareness while supporting intake growth. This study contributes to developing public relations theory in higher education and provides practical alternatives for university promotion strategies.